FAKTOR YANG MEMPENGARUHI MINAT MAHASISWA MEMILIH PROGRAM STUDI AKUNTANSI DI FAKULTAS EKONOMI DAN BISNIS ISLAM IAIN PAREPARE - indriani, indriani; Syarifuddin, Ahmad Dzul Ilmi (Program Studi Akuntansi Lembaga Keuangan Syariah, FEBI, IAIN Parepare, 2023)
This research aims to determine the extent of the influence of these factors on student interest. This research method is quantitative research with the type of field research. This research approach is associative which aims to explain the relationship between two or more variables. Determination of samples using the Cluster Sampling method. totaling 63 respondents from a total population of 587. The data source was obtained from filling out a questionnaire by the sample in the study. The data analysis technique used is the T test, multiple linear regression test and coefficient of determination test using the SPSS 26 program. Based on the results of the hypothesis testing research, it partially shows that family and promotion factors do not significantly influence student interest. Job opportunity factors and personal potential have a positive and significant effect on student interest.